Adhesive and Hydrophobic Bilayer Hydrogel Enabled On‐Skin Biosensors for High‐Fidelity Classification of Human Emotion. (22nd April 2022) - Yang, Ganguang; Zhu, Kanhao; Guo, Wei; Wu, Dongrui; Quan, Xueliang; Huang, Xin; Liu, Shaoyu; Li, Yangyang; Fang, Han; Qiu, Yuqi; Zheng, Qingyang; Zhu, Mengliang; et al.
Abstract: Traditional human emotion recognition is based on electroencephalogram (EEG) data collection technologies which rely on plenty of rigid electrodes and lack anti‐interference, wearing comfort, and portability. Moreover, a significant distribution difference in EEG data also results in low classification accuracy. Here, on‐skin biosensors with adhesive and hydrophobic bilayer hydrogel (AHBH) as interfaces for high accuracy emotion classification are proposed. The AHBH achieves remarkable adhesion (59.7 N m −1 ) by combining the adhesion mechanism of catechol groups and electrostatic attraction. Meanwhile, based on the synergistic effects of hydrophobic group rearrangements and surface energy reduction, the AHB‐hydrophobic layer exhibits 133.87° water contact angles through hydrophobic treatment of only 0.5 h. Hydrogen and electrostatic bonds are also introduced to form a seamless adhesive‐hydrophobic hydrogel interface and inhibit adhesion attenuation, respectively. With the AHBH as an ideal device/skin interface, the biosensor can reliably collect high‐quality electrophysiological signals even under vibration, sweating, and long‐lasting monitoring condition. Furthermore, the on‐skin electrodes, data processing, and wireless modules are integrated into a portable headband for EEG‐based emotion classification. A domain adaptive neural network based on the transfer learning technique is introduced to alleviate the effect of domain shift and achieve high classification accuracy. Abstract : A novel adhesive and hydrophobic bilayer hydrogel (AHBH) is developed as ideal device/skin interfaces for on‐skin electrodes. The biosensors can reliably collect high‐quality electrophysiological signals even under harsh conditions. By further combining domain adaptive neural network algorithms, a portable headband integrated with AHB hydrogel electrodes and wireless modules achieves high‐accuracy electroencephalogram‐based emotion classification.